Character Value Integration in Project-Based Learning for Developing Cooperation Skills of Wood Engineering Students - Zahrotul Isti'anah Marroh Marroh; Ita Merni Patulak; Andi Achmad; Muhammad Tahrir; Teguh Rizali Zahroni; Muhammad Akshar; Syafi'i Syafi'i; Abdul Rasyid Zarta; Luluk Humairo Pimada; Rangga Zanwil Solihin; Nurul Khatimah; Fatmawati Fatmawati; Nur Maulida Sari; Eva Nurmarini (Poltanesa, 2026)
Project-based learning (PBL) has been increasingly adopted in vocational higher education as a pedagogical approach that integrates technical skill development with interpersonal competency formation. However, the role of cultural and religious character values in shaping student cooperation within PBL environments remains underexplored, particularly in the Indonesian vocational context. This research examines how Islamic character values, namely amanah (trustworthiness), ta'awun (mutual assistance), and musyawarah (deliberation), were expressed and reinforced within the PBL structure implemented in the Wood Engineering study at Politeknik Pertanian Negeri Samarinda, and how this contributed to the development of student cooperation skills. A qualitative descriptive case study was employed, involving 44 fourth-semester students in eleven working groups across multiple wood engineering courses. Data were collected through structured in-depth interviews, participatory observation across 32 sessions, eleven focus group discussions, and document analysis. Thematic analysis following Braun and Clarke six-phase framework was applied, with inter-rater reliability of Cohen Kappa 0.86. Findings suggest that the project structure created favorable conditions for the expression and reinforcement of these character values, though the degree of internalization varied considerably across groups and individual students. The study contributes an empirically grounded illustration of how Islamic character values and cooperative behavior interact within authentic vocational project work, while acknowledging the context-specific nature of the findings